(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses the correctional-pedagogical significance of using didactic games in forming mathematical concepts in primary school pupils with intellectual disabilities. The article analyzes the role of didactic games in developing pupils’ concepts of number, counting, quantity, geometric shapes, space, and time. It also substantiates the possibilities of developing children’s cognitive activity, attention, memory, perception, speech, fine motor skills, and logical thinking in the process of game-based learning. Didactic games are considered an effective method that helps children with intellectual disabilities master educational material in an interesting, understandable, and practical way